Factors Related to Suicide Idea in the Rural Area of Indonesia - Eka, Angelina; Meku, Fransiskus S; Iwa, .Kornelia R; Krowa, Yuliana R R; Nggarang, Bonavantura N (Universitas Airlangga, 2024)
Background: People in rural areas in Indonesia have many challenges and problems that lead to psychosocial. The lack of mental health facilities and services result in severe mental issue like depression which can lead to suicide. Thus, Suicide can be prevented if the Suicide idea is detected. Unfortunately, there are few studies regarding factors related to suicide idea in rural areas especially in Indonesia, even though suicide rates in rural areas are often greater than in urban areas. This study wanted to look at the factors influencing Suicide ideas in rural Indonesia in Manggarai Regency. Method: This research is quantitative research using the cross-sectional approach. Respondents in the study were 150 people with inclusive criteria of 17 years and over and were willing to fill out questionnaires distributed online through Google Forms. Data collection was conducted using the Beck Suicide Idea Questionary, Beck Depression Scale, the Rosenberg Self-Esteem Scale, and Social Support Questionary Questionnaires tested for validity and reliability. Data analysis was carried out by logistic regression. Results: The results showed that the factors that influence Suicide ideas in rural areas of Indonesia are age (P-value: 0.04, OR: 0.18), depression (P value: 0.000, OR: 3.41), self-esteem (P value: 0.001 OR: 0.19), and social support (P-value: 0.002 OR: 0.2). The results of the multivariant analysis showed that the most variable influencing Suicide idea was depression (P-value: 0.000 and OR: 4.9) which means people with major depression have 4.9 times stronger Suicide idea. Conclusion: In providing prevention education to clients with suicide, health professionals including nurses can emphasize the importance of family and environmental support, especially in adolescents.